On the integrated design of curvilinearly grid-stiffened panel with non-uniform distribution and variable stiffener profile. (May 2020) - Liu, Dachuan; Hao, Peng; Zhang, Kunpeng; Tian, Kuo; Wang, Bo; Li, Gang; Xu, Weixiu
Abstract: In this paper, the integrated design of curvilinearly grid-stiffened panels is investigated, including stiffener layout design and profile design. The layout design includes the curvilinear path and non-uniform distribution of stiffeners. Firstly, the path of curvilinear stiffeners is defined by the piecewise linear function, and the non-uniform distribution of curvilinear stiffener cluster is described by the proposed representation method based on the PCHIP interpolation function. In addition to the layout design, the variable profile design method of grid-stiffened structures is also proposed in this paper. The variations of the thickness and height of stiffeners are represented by curves respectively. Similarly, the variable profile design of stiffeners is realized by designing the curves. On this basis, various novel configuration of curvilinearly grid-stiffened panels can be obtained by the integrated layout and profile design. The effectiveness of the proposed integrated design framework is validated by numerical examples. Compared with the initial design, the final integrated design improves the critical buckling factor of the grid-stiffened panel by 73.09%, which shows a great design potential of this kind of variable-stiffness structure compared to constant-stiffness structures. Graphical abstract: Unlabelled Image Highlights: An efficient layout representation method of curvilinearly grid-stiffened panel with non-uniform distribution is proposed. A concept of variable profile design of stiffeners based on interpolation curve is proposed. Various novel configuration of curvilinearly grid-stiffened panels can be obtained by the integrated design framework.